Planar waveguide laser at 705 nm based on Eu:KY(WO4)2 epitaxial layer - Baillard Amandine; Bae Ji Eun; Loiko Pavel; Solé Rosa Maria; Aguiló Magdalena; Díaz Francesc; Brasse Gurvan; Mateos Xavier; Camy Patrice (EPJ Web of Conferences)
We report on polarized spectroscopy and deep-red laser operation of heavily Eu3+-doped KY(WO4)2 epitaxial layers. The waveguide laser delivered 7 mW at 705 mW with a linear polarization and a laser threshold of 22 mW.